Montmorillonite K10 (M-MMT K10) Modified With Metal Cations As Heterogeneous Catalysts For Esterification Reaction - Enas A.Almadani Alsanusi
Montmorillonite K10 (MMT K10), a major clay mineral commercially available can be treated to improve its properties and thus can be utilized for a broad range of organic reactions including esterification of free fatty acids for biodiesel production. However, the use of unmodified MMT K10 in esterification of fatty acids showed that the acid conversion was less than 60 % and this is not preferable to the production of biodiesel. The aim of this study is to utilize the available material i.e. MMT K10 clay as catalyst for the esterification of acetic acid and stearic acid. MMT K10 was treated using cation exchange processes with ions of (A13+,Fe3+ and Cu2+ ), then the prepared catalysts were characterized using several techniques. Their catalytic activities were tested for esterification reaction of stearic acid and acetic acid with two different alcohols i.e. ethanol and methanol. Response surface methodology (RSM) was implemented to optimize the esters production. The Fourier transform infrared (FTIR) spectra showed that the bands for -OH vibrations in MMT K10 shifted to higher wavenumbers and this indicated that the absorbed water in MMT K10 was decreased by the exchanged cations and then the clay surface became more hydrophobic. Energy-dispersive X-ray spectroscopy (EDX) data proved that the cation exchange process between the Mg2+ions (exchangeable cation) and the guest ions ( A13+,Fe3+ and Cu2+) has occurred on the surface of MMT K10 clay. The cations also were found to fill in the pore and largely distributed on the surface of MMT K10 based on the surface analysis that caused the decrease in the surface area of all modified MMT K10 samples from 228.29 m2/g to 195.54, 175.78 and 172.01 m2/g for 0.75 M Fe-MMT Kl0, 0.75 M Al-MMT K10 and 0.75 M Cu-MMT K10 respectively. Prepared catalysts were able to give the highest acid conversions of up to 78% due to increase their Lewis acidity relative to the unmodified MMT K10 from 0.61 in MMT K10 to 0.87, 1.13 and 1.55 in Al-MMT K10, Fe-MMT K10 and Cu-MMT K10 respectively. Cu-MMT K10 samples showed the highest Lewis acid sites value =compared to Al-MMT K10 and Fe-MMT K10 samples, as the Cu is a divalent cation with large ion size and this caused the acceptance of a pair of electron from nitrogen atom of the pyridine molecule which resulted in the Lewis interaction. The esterification of stearic acid with methanol using 0.75 M Cu-MMT K10 at 80 OC during the 3 hours of reaction time showed the highest acid conversions of 78 %. Comparison between predicted and experimental values of esters products from the RSM analysis revealed a good correspondence between them, thus indicating the suitability of the models developed and the success of RSM in optimizing the esters production.